ANALISIS NILAI SOSIOLOGIS CERITA EMAS DI DOLOK PINAPAN DAERAH PULO GODANG, KEC. PAKKAT, KAB. HUMBANG HASUNDUTAN - Evi Melpa L. Gaol (Basastra, 2013)
Sociology and literature alike outlining the problem. Man's relationship with his family, environment, customs-customs, and others. Furthermore sociology as a science that tries to express the social problems again. Gold in Dolok Pinapan story is one form of oral literature Toba Batak community property, which is precisely Pulogodang, Pakkat District, District Humbang Hasundutan. This study aimed to describe the composition of the stories and events that happened in the legend Pulogodang, structured and translated into a story and explore the values ​​contained therein sociology. This research is a qualitative descriptive study, prioritize the meaning and context, the role of researcher of high demand. Informants in this study there were 6 people in the two cultural experts Pulogodang, one king custom in Pulogodang, three people Pulogodang.Temuan end of study was sociology there are three values ​​that are relevant to today's society, and one is no longer relevant sociological value Batak Toba.   Keywords: Sociology of Literature, Stories, and community